The urban archetypes of Jane Jacobs and Ebenezer Howard : contradiction and meaning in city form - Akkerman, Abraham, 1948- (University of Toronto Press, 2020)
"This monograph brings the urban planning approaches of Howard and Jacobs into a single urbanist context. It identifies pints of contrast as well as commonalities between the two approaches by setting them first onto a paradigmatic level of prime environmental archetypes that have shaped city form since archaic times. Through the examination of various urbanist and urban planning approaches throughout the 20th century both Howard and Jacobs are shown as steadfast albeit imperfect chaperones of the enviromental archetypes of the Farden and the Citadel for the idea city."--